2020
DOI: 10.3390/cells9020393
|View full text |Cite
|
Sign up to set email alerts
|

Myelin Measurement Using Quantitative Magnetic Resonance Imaging: A Correlation Study Comparing Various Imaging Techniques in Patients with Multiple Sclerosis

Abstract: Evaluation of myelin by magnetic resonance imaging (MRI) is a difficult challenge, but holds promise in demyelinating diseases, such as multiple sclerosis (MS). Although multiple techniques have been developed, no gold standard has been established. This study aims to evaluate the correlation between synthetic MRI myelin volume fraction (SyMRIMVF) and myelin fraction estimated by other techniques, i.e., magnetization transfer saturation (MTsat), T1-weighted images divided by T2-weighted images (T1w/T2w), and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 54 publications
6
40
0
Order By: Relevance
“… 1 Quantitative synthetic MRI is typically performed through a commercial 2-dimensional (2D) multidynamic multiecho (MDME) sequence, providing simultaneous quantification of T1, T2, and PD, with a scan time of about 5 to 6 minutes for full head coverage. 16 Quantitative synthetic MRI has enabled objective evaluation of diseases such as Alzheimer disease, 19 multiple sclerosis, 20 22 brain infarction, 23 brain tumor, 24 , 25 and Sturge-Weber syndrome. 26 Using dedicated software, we can also automatically obtain brain parenchymal volume (BPV), white matter volume (WMV), and gray matter volume (GMV), based on these quantitative values.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 1 Quantitative synthetic MRI is typically performed through a commercial 2-dimensional (2D) multidynamic multiecho (MDME) sequence, providing simultaneous quantification of T1, T2, and PD, with a scan time of about 5 to 6 minutes for full head coverage. 16 Quantitative synthetic MRI has enabled objective evaluation of diseases such as Alzheimer disease, 19 multiple sclerosis, 20 22 brain infarction, 23 brain tumor, 24 , 25 and Sturge-Weber syndrome. 26 Using dedicated software, we can also automatically obtain brain parenchymal volume (BPV), white matter volume (WMV), and gray matter volume (GMV), based on these quantitative values.…”
mentioning
confidence: 99%
“… 28 Myelin volume fraction derived from quantitative synthetic MRI has been validated by postmortem imaging 29 , 30 and comparison with other myelin imaging techniques. 22 , 31 …”
mentioning
confidence: 99%
“…Because many myelin-specific imaging techniques are available, it is possible that different types of myelin-sensitive imaging might show different results. [33][34][35][36] Given the complicated postprocessing, myelin imaging may not be practical for routine application in clinical settings compared with conventional diffusion parameters (On-line Table 2). Despite these limitations, this study is the first to directly investigate myelin damage using a myelin-sensitive MR imaging technique in adult patients with MMD and its relationship with cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous studies using the T1w/T2w showed a strong correlation with myelin volume fraction in human WM (Saccenti et al, 2020), oligodendrocyte-specific gene expression in humans (Patel et al, 2020), and with cortical myelin as compared to histological myeloarchitectural studies in both humans and non-human primates (Glasser & van Essen, 2011). However, others have found that the T1w/T2w correlated with MRI estimates of axonal diameter (Arshad et al, 2017), axonal density (Fukutomi et al, 2018), and iron content in healthy adults (Shams et al, 2019).…”
Section: T1w/t2w As An Index Of Wm Healthmentioning
confidence: 96%